2013
DOI: 10.1111/j.1468-2435.2009.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Ties During a Time Of Crisis: Israeli Emigration, 2000 To 2004

Abstract: Despite their impressive patterns of economic mobility and generally successful adaptation into Western host societies, Israeli emigrants frequently view their stay abroad through the perspective of Zionism. As such, they express ambivalence about their presence on foreign soil. They seldom describe themselves as host country nationals, commonly socialize with other Israelis, frequently describe their intentions to return home, and often do so. However, recent events may challenge this outlook. During the 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…4 immigration and emigration have been replaced in Israel by value laden terms having positive connotations from immigrants and negative one for emigrants" (Cohen, 1988: 909). Gold and Hart (2013) claim that Israeli migrants (the Israeli diaspora) tend to resist full integration into the host societies, viewing their stay abroad as a temporary venture due to Zionist ideology which demands that Jews should live in their historical homeland, the state of Israel. However, recent studies on Israeli emigration (Gold & Hart, 2013;Harris, 2015) have found increased migration of highly skilled and educated Israeli-born population, and argued that the rationales for migration are no longer purely financial but also display ideological motivations, specifically in relation to a disapproval of current right-wing governments' approach to managing the Palestinian-Israeli conflict, and a lack of hope that it will ever be resolved.…”
Section: The Study Contextmentioning
confidence: 99%
“…4 immigration and emigration have been replaced in Israel by value laden terms having positive connotations from immigrants and negative one for emigrants" (Cohen, 1988: 909). Gold and Hart (2013) claim that Israeli migrants (the Israeli diaspora) tend to resist full integration into the host societies, viewing their stay abroad as a temporary venture due to Zionist ideology which demands that Jews should live in their historical homeland, the state of Israel. However, recent studies on Israeli emigration (Gold & Hart, 2013;Harris, 2015) have found increased migration of highly skilled and educated Israeli-born population, and argued that the rationales for migration are no longer purely financial but also display ideological motivations, specifically in relation to a disapproval of current right-wing governments' approach to managing the Palestinian-Israeli conflict, and a lack of hope that it will ever be resolved.…”
Section: The Study Contextmentioning
confidence: 99%
“…Some point to the heavy toll that the Second Intifada, which began in 2000, had on Israeli society and the Israeli economy. In other words, they suggest that this hardship made leaving Israel more understandable, and indeed, there has been a dramatic rise in Israeli migration since the intifada began (Gold and Hart, 2009; Lustick, 2004; Statistics Canada, 2007b). The tough times of the Second Intifada, however, cannot alone explain a drop in the guilt and stigma of yerida .…”
Section: Explaining Changing Attitudes On Migrationmentioning
confidence: 99%
“…To learn about the experience of Israeli immigrants, I worked in conjunction with five Hebrew-speaking women research assistants to collect several forms of data between June 1991 and July 2004 (Gold 2002; Gold and Hart 2009). A major source was 194 in-depth interviews (conducted in both Hebrew and English) with Israeli immigrants and others knowledgeable about their community in the Los Angeles area (87 women and 107 men, including both the wife and husband of twenty couples).…”
Section: Methodsmentioning
confidence: 99%
“…Such events reduced the quality of public life and made economic conditions for many worse. Finally, the Israeli government reduced various forms of social spending, improving circumstances for investors and entrepreneurs, but making services and advanced education more difficult to obtain for the less affluent (Gold and Hart 2009). Accordingly, even as Israel’s InfoTech sector blossomed, conditions for some factions of Israeli society have become austere, thus increasing the number living abroad (Cohen 2011; Gold and Hart 2009; Senor and Singer 2009).…”
Section: Environments Of Immigrant Women’s Self-employmentmentioning
confidence: 99%